2011
DOI: 10.4034/pboci.2011.111.02
|View full text |Cite
|
Sign up to set email alerts
|

Análise Morfológica da Mucosa Oral de Ratos Submetida à Carcinogênese Experimental pelo Óxido de Nitroquinolina (4NQO)

Abstract: Ratos wistar; Carcinoma in situ; Carcinoma de células escamosas. Wistar rats; Carcinoma in situ; Squamous cell carcinoma. Objecti ve: To induce carcinogenesis on the lingual mucosa of Wistar rats by the administrati on of nitroquinoline oxide (4NQO), relati ng the clinical and microscopic alterati ons developed during the ti me of exposure to the carcinogenic agent. Methods: Twenty rats were allocated to either an experimental (15 animals) or a control (5 animals) group. In the experimental group, the animals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…Our findings also confirm that the tongue region to be analyzed is essential in this experimental model, as the histopathological changes were observed exclusively in the mid-and posterior portions of the tongue (5). The results of the descriptive histopathological assessment of the mid-and posterior regions of the tongue confirm the findings of previous studies showing the presence of atypical cells and epithelial dysplasia after 8 weeks of exposure to 4-NQO.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Our findings also confirm that the tongue region to be analyzed is essential in this experimental model, as the histopathological changes were observed exclusively in the mid-and posterior portions of the tongue (5). The results of the descriptive histopathological assessment of the mid-and posterior regions of the tongue confirm the findings of previous studies showing the presence of atypical cells and epithelial dysplasia after 8 weeks of exposure to 4-NQO.…”
Section: Discussionsupporting
confidence: 89%
“…4‐Nitroquinoline oxide is a carcinogen routinely used to study oral carcinogenesis in rodents. Most commonly, 4‐NQO is used by topical application or administered systemically in the drinking water . The route of administration and dosage of 4‐NQO employed in this study were based on previous studies, which were shown to be well tolerated and pharmacologically active in inducing oral cancer in rats .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations